Prime Minister Narendra Modi visit to Sri Lanka and its impacts on Indo-Sri Lankan relations - Jeeva, S.; Sivakumar, D. (Linguistics and Culture Review, 2021)
In Globe, no nation is not an isolate it depends upon one another to fulfill their needs as a result of these multilateral relations build-up. Such a strong relationship we need to maintain means we need strong leadership. Such strong leaders are there before and after independence also. The several party leaders and their alliances are formed and implemented the policies for the development of India at the Internal level as well as external level. The National Democratic Alliance (NDA) government was formed under two prominent leaders known as Atal Bihari Vajpayee and Narendra Modi. After Vajpayee, the NDA Government under the leadership of Narendra Modi realized the importance of foreign policy and maintaining a good relationship. Sri Lanka is also one of the closest neighboring countries; Prime Minister Narendra Modi from 2014 to 2019 he officially visited Sri Lanka three times within these three visits he used to make several new initiatives in many fields.